2021
DOI: 10.1021/acs.nanolett.0c05117
|View full text |Cite
|
Sign up to set email alerts
|

Intertwined Topological and Magnetic Orders in Atomically Thin Chern Insulator MnBi2Te4

Abstract: MnBi2Te4, a van der Waals magnet, is an emergent platform for exploring Chern insulator physics. Its layered antiferromagnetic order was predicted to enable even–odd layer number dependent topological states. Furthermore, it becomes a Chern insulator when all spins are aligned by an applied magnetic field. However, the evolution of the bulk electronic structure as the magnetic state is continuously tuned and its dependence on layer number remains unexplored. Here, employing multimodal probes, we establish one-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
145
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 29 publications
15
145
0
Order By: Relevance
“…The existence of a metallic bulk state during the transition is corroborated by our bulk transport measurement as well (see supplementary information S3). The evolution of bulk conductivity as a function of magnetic field was reported in another work with similar results 28 .…”
Section: Resultssupporting
confidence: 81%
“…The existence of a metallic bulk state during the transition is corroborated by our bulk transport measurement as well (see supplementary information S3). The evolution of bulk conductivity as a function of magnetic field was reported in another work with similar results 28 .…”
Section: Resultssupporting
confidence: 81%
“…Recently, two independent studies reported unusual layer-dependent magnetic properties in MBT devices, 56 , 57 observing anomalous magnetic hysteresis loops in polar reflective magnetic circular dichroism spectroscopy results 56 and anomalous Hall curves in even-layer MBT. 57 More intriguingly, Ovchinnikov et al . 57 found that the hysteresis loop near zero magnetic field vanished for an odd-layer device in the AFM state.…”
Section: Observation Of Axion Insulatormentioning
confidence: 99%
“… 57 More intriguingly, Ovchinnikov et al . 57 found that the hysteresis loop near zero magnetic field vanished for an odd-layer device in the AFM state. Actually, most device samples in experiments are inevitably affected by various factors during device fabrication process and measurements, including sample quality and oxidation.…”
Section: Observation Of Axion Insulatormentioning
confidence: 99%
“…Furthermore, upon applying a magnetic field to control the arrangement of the interlayer spins in MnBi2Te4, the states of QAH insulators and axion insulators become interchanged [11][12][13][14][15][16][17][18][19][20]. Axion insulators and Chern insulators have recently been realized in mechanically exfoliated MnBi2Te4 flakes [12,[21][22][23], but such flakes are fragile and have small and irregular shapes, thus preventing the large-scale fabrication of devices that utilize the QAH effect. Moreover, the fabrication of MnBi2Te4 flakes requires heating to a high temperature, which readily causes high-density intrinsic defects.…”
Section: Introductionmentioning
confidence: 99%